Analisis Hambatan Belajar Pada Materi Sistem Persamaan Dan Pertidaksamaan Linear Satu Variabel Di SMP Negeri 2 Tatapaan - Axel Fricly Lompande; Philoteus E.A. Tuerah; Derel Filandy Kaunang (Journal on Education, 2024)
This research was conducted to find out what factors hinder the learning of class VII students of SMP Negeri 2 Tatapaan for the 2023/2024 academic year on the material Systems of Linear Equations and Inequalities in One Variable. The population and sample of this research is 40. This research is a quantitative descriptive research that uses survey methods and data collection using research instruments in the form of questionnaires and interviews. The questionnaire created had 24 statement items. The results of the research show that the internal aspects of learning barriers in the One Variable System of Linear Equations and Inequalities material fall into the Moderately Obstructed category (65.74%), with the lowest indicator being student readiness which falls into the Quite Impeded category (48%). Furthermore, the external aspect of barriers to student learning in the material Systems of Linear Equations and Inequalities with One Variable was included in the Moderately Obstructed category (68.6%), with the lowest indicator being Family, which was included in the Moderately Obstructed category (55.5%).